Avaliação dos Defumadores: Vertical Estático e Horizontal Rotativo para o Pacu (Piaractusmesopotamicus) e Armado (Pterodoras granulosus) - Debona, Francielli Maria Vanin (2015)
This study aimed to develop a smoked product to fish-based, with reference to the pacu (Piaractusmesopotamicus) and the armado (granulosus Pterodoras), freshwater fish abundant in southern Brazil. We evaluated two treatments in the smoking process: static upright smoker and the flat rotative smoker. To carry out the smoking process, the fish were subjected to brine salting at a concentration of 15% for about two hours and soon after placed in different smokers. Performance tests were carried out in pacu and armado in natura 71.09%, 47.80% respectively. The pacu showed the best performance after the smoking process in the flat rotating smoker (80%) compared to the static vertical smoker (73%). Already armed presented in 67% yield on the rotary flat smoker and 60% in the static vertical smoker. In addition to these tests, physical-chemical analyzes were carried out moisture, protein, lipid, ash and energy (Cal / g) and pH. The Pacu and smoked armado in static upright smoker obtained moisture content (47.87%, 62.78%), protein (46.51%, 64.54%), lipids (41.21%, 23.55% ), energy (Cal / g) (6695, 5524 Cal / g). However pacu and smoked armed in rotating horizontal smoker did better as the levels of: moisture (55.24%, 63.35%), protein (58.06%, 67.32%), lipids (31.08 % 16,08) and energy (Cal / g) (6011, 4967 Cal / g). The microbiological analyzes performed in the raw material in natura and in the end product, it was for all and faecal coliforms, Salmonella spp, Staphylococcus aureus, mesophilic, molds and yeasts. Both samples were within the standards established by Brazilian law to the period of 19 days after the smoking process and kept refrigerated at 4 ° C. Samples of smoked fish in different treatments were subjected to sensory analysis and the end product, which achieved a significant difference between the two treatment and the two species. The product has obtained the highest marks was the smoked pacu in rotary flat smoker. The results proved the feasibility of smoking on the rotary flat smoker